Alkenone sea surface temperature estimates of gravity core M40/4_SL67 (eastern Mediterranean Sea) - Kay-Christian Emeis; Ulrich Struck (PANGAEA, 2022)
Water column stratification increased at climatic transitions from cold to warm periods during the late Quaternary and led to anoxic conditions and sapropel formation in the deep eastern Mediterranean basins. Here we report downcore sea surface temperature estimates of gravity core M40-4/67 taken in the region of the Rhodes Gyre (eastern Mediterranean Sea) that elucidate the influence of glacial/interglacial temperature changes in determining density of surface waters and formation of sapropels.